ANALISIS PROBLEMATIKA PENERAPAN KURIKULUM MERDEKA DI SEKOLAH DASAR - Nelsya Putri Zalianti; Cahya Putriani; Dyan Elsa Putri; Rizki Ananda; Nasrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to thoroughly identify the problems that arise when implementing an independent curriculum in an elementary school environment. The research method used in this research is a descriptive qualitative research method with a library study approach, which is research by searching and collecting data from sources such as relevant books and journals. The results of research on the problems of implementing the independent curriculum in elementary schools identified a number of problems which include teachers' difficulties in formulating the flow of learning objectives, lack of mastery of technology in the learning process, difficulties in developing learning models that are in accordance with the independent curriculum, and inadequate availability of facilities and infrastructure. To overcome this problem, there are several solutions proposed including holding teacher training, carrying out outreach, utilizing the Merdeka Belajar platform, repairing and upgrading facilities and infrastructure, carrying out supervision and monitoring, as well as increasing collaboration between education stakeholders. It is hoped that these solutions can increase the effectiveness of implementing the independent curriculum in elementary schools. Keywords: Curriculum, Freedom to Learn